Unchecked corporate power: why the crimes of multinational corporations are routinized away and what we can do about it - Barak, Gregg (Crimes of the powerful, 2017)
pt. I. Routinizing the crimes of the powerful -- pt. II. Violating the commons -- pt. III. Halting corporate harm.